Dermoscopy of papulopustular rosacea and comparison of dermoscopic features in patients with or without concomitant Demodex folliculorum. (6th September 2021) - Trave, I.; Micalizzi, C.; Gasparini, G.; Cozzani, E.; Parodi, A.
Summary: Background: The dermoscopic findings of papulopustular rosacea include tiny papules and pustules, follicular plugs and follicular dilatation. Demodex tails and Demodex follicular openings are dermoscopic indicators that are mainly found in primary demodicosis and, less frequently, in rosacea. Aim: To describe the dermoscopic features of papulopustular rosacea and to investigate the differential dermoscopic features between patients with and without concomitant Demodex infestation. Methods: We conducted a prospective study of patients with almost‐clear, mild or moderate papulopustular rosacea. For each patient, dermoscopic images were taken and a standardized skin surface biopsy was performed. Results: In this group of 60 patients, the most frequent dermoscopic findings were yellow dots, vascular polygons and follicular scales. Patients with moderate rosacea had more Demodex follicular openings compared with patients with mild rosacea ( P  = 0.02), while patients with mild rosacea had a higher frequency of follicular scales than did patients with almost‐clear rosacea ( P  = 0.01). Patients with moderate rosacea had higher rates of Demodex follicular openings ( P  = 0.02), follicular scales ( P  < 0.001), follicular annular pigmentation ( P  = 0.001) and follicular pustules ( P  < 0.001) compared with patients with almost‐clear rosacea. No significant dermoscopic differences were observed between patients with and without concomitant Demodex infestation. Conclusions: Papulopustular rosacea has specific dermoscopic findings. In our opinion, dermoscopy is not sufficient by itself for the diagnosis of Demodex proliferation in rosacea.